Analysis of Argumentation Contents in the High School Biology Textbook: A Discourse Analysis on the Topic of the Respiratory System - Rosliana, Ria; Suyanto, Slamet (FKIP Universitas Lampung, 2022)
Analysis of Argumentation Contents in the High School Biology Textbook: A Discourse Analysis on the Topic of the Respiratory System. Objectives: Study examines structure of learning discourse, explores aspects of discussion, examines presentation of learning motives in textbooks, analyzes a comparison of three biology textbooks on respiratory materials. Methods: A qualitative investigation of descriptive text kinds from late-XI biology textbooks, discourse structure analysis tasks, conversational type elements, learning motive explanations. Findings: Publishers: Erlangga, Yrama Widya, Intan Pariwara. Conclusion: Results revealed nature of conversation structure. Three scientific books observed that one side of the argument swamped any remaining sections of debate due to a rapid review of doubtful material. Examining three books analysed reveals a discussion of many quality,rating issues. In Good category, Book B got highest rating of 8.3. Book C received an 8.2 on the